2017
DOI: 10.18609/cgti.2017.005
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the use of ZFN-mediated gene editing for human gene therapy

Abstract: Targeted genome editing with programmable nucleases has revolutionized biomedical research. The ability to make site-specific modifications to the human genome, has invoked a paradigm shift in gene therapy. Using gene editing technologies, the sequence in the human genome can now be precisely engineered to achieve a therapeutic effect. Zinc finger nucleases (ZFNs) were the first programmable nucleases designed to target and cleave custom sites. This article summarizes the advances in the use of ZFN-mediated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
0
25
0
1
Order By: Relevance
“…The main characteristics of the designer nucleases [11][12][13][14] Guanine-rich region The ability to recognize any certain sequence of DNA triplets; Small protein size High-priced, labor-intensive, and timetaking; Unintended change in DNA; restricted target length to multiples of three; laborious zinc finger engineering and sequence selection TALEN Recently, Anzalone et al 22 have reported construction of a searchand-replace genome editing CRISPR based method, named prime editing, which consist of a catalytically impaired Cas9 fused to an engineered reverse transcriptase, employing a prime editing guide RNA (pegRNA) with the ability to specify the target sequence and edit the favored position. Nickase Cas9 (nCas9) proteins are another form of Cas9 modifications involving a single mutated nucleolytic domain while the other domain preserves its cleavage activity and therefore produce single strand breaks (SSBs).…”
Section: T a B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the designer nucleases [11][12][13][14] Guanine-rich region The ability to recognize any certain sequence of DNA triplets; Small protein size High-priced, labor-intensive, and timetaking; Unintended change in DNA; restricted target length to multiples of three; laborious zinc finger engineering and sequence selection TALEN Recently, Anzalone et al 22 have reported construction of a searchand-replace genome editing CRISPR based method, named prime editing, which consist of a catalytically impaired Cas9 fused to an engineered reverse transcriptase, employing a prime editing guide RNA (pegRNA) with the ability to specify the target sequence and edit the favored position. Nickase Cas9 (nCas9) proteins are another form of Cas9 modifications involving a single mutated nucleolytic domain while the other domain preserves its cleavage activity and therefore produce single strand breaks (SSBs).…”
Section: T a B L Ementioning
confidence: 99%
“…ZFN-mediated CCR5 disruption, was the first application of genome editing tools in human in order to prevent the entry of HIV into the cells. 12 Table 1 summarizes the main properties of this nuclease along with the other genome editing tools. The key for opening the third gate to the gene editing world was in the hands of a plant pathogen called Xanthomonas which in 2009 was discovered to have DNA sequence specific transcription activator-like effector (TALE) proteins 19 with each repeat domain having the ability to distinguish a single base.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid replacement in DNA-binding proteins from ZFNs has also been a topic of interest for research. 18 Nevertheless, increasing the efficiency of ZFNs, as a tool that facilitates genetic manipulation for purposes such as the development of novel human disease models and gene therapy strategies, is still a matter of debate (Table 1).…”
Section: Zfnmentioning
confidence: 99%
“…In a study recently carried out aiming to improve specificity and reduce toxicity, an increase in the number of ZF motifs, as well as the inactivation of the catalytic component of ZFNs, was shown that lead to the creation of an enzyme called ZF nickase. Amino acid replacement in DNA‐binding proteins from ZFNs has also been a topic of interest for research . Nevertheless, increasing the efficiency of ZFNs, as a tool that facilitates genetic manipulation for purposes such as the development of novel human disease models and gene therapy strategies, is still a matter of debate (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the higher the nuclease specificity, the lower the nuclease off-target cleavage and henceforth associated-toxicity. 104 Several studies highlighted the fact that the existent analogous architecture between ZFNs and TALENs seemed preponderant to achieve a fruitful clinical setting through the development of the following mutual nuclease-criteria: 105 A. High specificity of the DNA-binding domain…”
Section: Refining Zfns and Talens: Specificity And Toxicitymentioning
confidence: 99%